La Follette family papers (primary record) - La Follette, Belle Case, 1859-1931.; La Follette, Fola, 1882-1970.; La Follette, Mary Josephine, 1899-1988.; La Follette, Philip Fox, 1897-1965.; La Follette, Robert M. (Robert Marion), 1855-1925.; La Follette, Robert M. (Robert Marion), 1895-1953.; Lynch, Grace C., approximately 1892-1970.; Roe, Gilbert E. (Gilbert Ernstein), 1865-1929.; Rogers, Alfred Thomas, 1873-1948.; National Progressive Republican League
Correspondence, diaries, speeches, writings, legal files, office files, campaign files, legislative files, subject files, financial records, biographical material, newspaper clippings, printed material, and other papers principally documenting the careers of Robert M. La Follette, Sr., governor of Wisconsin and U.S. representative and senator, and his son Robert M. La Follette, Jr., U.S. senator.
Includes papers of Robert M. La Follette, Sr.; papers of Robert M. La Follette, Jr.; papers of Belle Case La Follette, lawyer, journalist, editor, and suffragist; papers of Fola La Follette, actress and educator; papers of Philip Fox La Follette, lawyer and governor of Wisconsin; and papers of Mary Josephine La Follette, art consultant, social science research analyst, and editor. Also includes papers of Grace C. Lynch, secretary to Robert M. La Follette, Sr., and to Robert M. La Follette, Jr.; papers of Gilbert E. Roe, New York lawyer and adviser to Robert M. La Follette, Sr.; papers of Alfred Thomas Rogers, law partner of Robert M. La Follette, Sr.; records of the National Progressive Republican League; and extensive files relating to La Follette's Magazine and to its successor, The Progressive.
Subjects include American Indian affairs, child labor laws, civil rights, conservation, disarmament, education, espionage, foreign relations especially with Latin America and Asia, freedom of assembly, freedom of the press, hygiene, immigration, isolationism, judicial reform, New Deal, peace movement, political primaries, presidential elections of 1912 and 1924, public lands, railroad regulation, reform lobbies, regulatory commissions, tariffs, taxation, the Teapot Dome scandal, U.S. political affairs, veteran's claims, Wisconsin politics, women's rights and suffrage, World Wars I and II, and outlawry of war. Also includes material concerning American handicrafts, Wisconsin attorney general Bronson C. La Follette, and family biographer Sherry Zabriskie.
Includes material pertaining to the Conference for Progressive Political Action, Emily Bishop League, League of Nations, National Conservation Association, National Consumers' League, National Council for Prevention of War, National League of Women Voters, National Municipal League, People's Legislative Service, Women's International League for Peace and Freedom, and other progressive and reform movements.
In addition to family members, correspondents include Jane Addams, Peter A. Arntson, Ray Stannard Baker, Charles Austin Beard, Mary Ritter Beard, Joseph D. Beck, Emily Montague Mulkin Bishop, Alice Stone Blackwell, John J. Blaine, W. Wade Boardman, Alice Goldmark Brandeis, Louis Dembitz Brandeis, William Jennings Bryan, Austin F. Cansler, James H. Causey, John Rogers Commons, Calvin Coolidge, Charles Richard Crane, Charles Henry Crownhart, Bronson M. Cutting, Jo Davidson, Thomas F. Davlin, Eugene V. Debs, Charles M. Dow, Theodore Dreiser, Herman Lewis Ekern, Elizabeth Glendower Evans, William Theodore Evjue, John D. Fackler, Lorena King Fairbank, Felix Frankfurter, Zona Gale, A.C. Grimm, John J. Hannan, Norman Hapgood, Frank A. Harrison, Herbert Hoover, Walter L. Houser, B. W. Huebsch, Ralph M. Immell, Helen Keller, William Kirsch, Walter Jodok Kohler, Irvine Luther Lenroot, Katharine F. Lenroot, David Eli Lilienthal, Edward G. Little, Henry Cabot Lodge, Alice Roosevelt Longworth, Grace C. Lynch, Joseph McCarthy, Medill McCormick, Thomas M. McCusker, Nellie Dunn MacKenzie, Basil Maxwell Manly, Wayne L. Morse, Sylvester W. Muldowny, Richard L. Neuberger, Richard M. Nixon, Cornelia Bryce Pinchot, Gifford Pinchot, William Thomas Rawleigh, Vinnie Ream, R.O. Richards, Glenn D. Roberts, Gilbert R. Roe, Gwyneth K. Roe, John Ernest Roe, Alfred Thomas Rogers, Walter S. Rogers, Franklin D. Roosevelt, Theodore Roosevelt, Morris H. Rubin, Upton Sinclair, Gordon Sinykin, Rudolph Spreckels, Lincoln Steffens, Isaac Stephenson, Bela Tokaji, Harry S. Truman, Arthur H. Vandenberg, Frank P. Walsh, William Allen White, Woodrow Wilson, Emma Wold, and A.W. Zeratsky.
Primary record for La Follette family papers. Continuation record mm2009085509 consists of the correspondents represented in the collection.
Library of Congress Prints and Photographs Division.
Prominent Wisconsin family in late nineteenth and twentieth century national politics.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: La Follette, Bronson C. -- 1936-; White, William Allen, -- 1868-1944.; Wilson, Woodrow, -- 1856-1924.; Wold, Emma, -- 1871-1950.; Zabriskie, Sherry; La Follette family; Emily Bishop League; League of Nations; National Conservation Association (U.S.); National Consumers' League; National Council for Prevention of War (U.S.); National League of Women Voters (U.S.); National Municipal League; People's Legislative Service; Women's International League for Peace and Freedom; La Follette's magazine; Progressive; Assembly, Right of; Child labor -- Law and legislation -- United States; Civil rights; Conservation of natural resources; Courts -- United States; Disarmament; Education -- United States; Espionage; Freedom of the press -- United States; Handicraft -- United States; Hygiene -- United States; Independent regulatory commissions -- United States; Indians of North America; Isolationism; Lobbying -- United States; Neutrality -- United States; New Deal, 1933-1939.; Peace movements -- United States; Presidents -- United States -- Election -- 1912.; Presidents -- United States -- Election -- 1924.; Primaries -- United States; Progressivism (United States politics); Public lands -- United States; Railroads and state -- United States; Tariff -- United States; Taxation -- United States; Teapot Dome Scandal, 1921-1924.; War; Women -- Suffrage; Women's rights; Veterans -- United States; World War, 1914-1918 -- United States; World War, 1939-1945 -- United States; Asia -- Foreign relations -- United States; Latin America -- Foreign relations -- United States; United States -- Economic policy -- 1933-1945.; United States -- Emigration and immigration; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- Asia; United States -- Foreign relations -- Latin America; United States -- Politics and government -- 1901-1953.; Wisconsin -- Politics and government